Exploring the Costume Styling and Material Composition of the Effutu Festival Costumes - Safo-Ankama, Kweku; Sawyerr, Naa Omai (International Journal of Culture and Art Studies, 2023)
This study investigates the costume styling and material composition of Effutu festival costumes. It is delimited to Effutu festival performance costumes. The qualitative design was adopted. The ethnography approach was employed through narrative analysis and oral history. Unstructured interviews and on-site direct observations were the qualitative data collection instrument used for the data collection. The narrative analysis was used to analyse the data. The findings revealed that historically costumes are seen as relics that can tell the story about the exploits and traditional mythologies of the communities. Again, costumes that materialise culture and identities do not just mirror pre-existing sets of ideas or symbolic systems but facilitate values as ‘they form part of an ethnohistorical repository of knowledge. The findings further revealed that, costume styling could be categorised into Royal, Ritual, Asafo (war/battle), Generational, Women ensembles (Adzewa costumes) and Fanciful costumes. The basic material composition of costumes includes fabrics (both applied and structural designs), leather, horsetail, metal helmets, pillows, kaolin, beads (plastic and glass), mpoboa (shoes), symbolic colours and other material collaboration. It is recommended that costumes used for the Effutu festival be recorded and digitalised for future reference.